Induction of parturition in crossbred sows with cloprostenol, an analogue of prostaglandin F2α - Jainudeen, M.R.; Brandenburg, A.C. (Elsevier, 1980)
Forty-six crossbred sows were treated with a single intramuscular injection of 175 μg of cloprostenol on day 110, 112 or 113 of gestation and compared with 46 control animals farrowing naturally during the same period. Of the treated animals, 96% farrowed within 48 h. The mean time to the induced farrowing was 28 ± 1.2 h with 64% of the farrowings occurring during daylight hours. Piglet mortality was greater for farrowings induced at day 110 than for 112 or 113 days of gestation. Since the mean length of gestation for natural farrowings for untreated control sows was 115 ± 0.9 days, it may be concluded that farrowings could safely be induced within 2-3 days of the average expected farrowing date for the herd. For precise timing of treatment, the average gestation length for individual herds should be pre-determined and accurate breeding records are needed.